TINJAUAN KETERDAPATAN BATUAN ULTRAMAFIK DALAM KOMPLEK OFIOLIT CILETUH DI DAERAH CILETUH, JAWA BARAT - Hutabarat, Johanes; -, Ismawan (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
Ultramafic rock is defined as rock with a color index of more than 70, and most have good characteristics as igneous plutonic and metamorphic rocks. Ultramafic rocks in the area Ciletuh revealed in outcrops scattered as